Do changing patterns of heat and humidity influence thermoregulation and endurance performance? - Cochrane, D. J.; Sleivert, G. G. (Journal of Science and Medicine in Sport, 1999)
The purpose of this project was to determine whether changing patterns of temperature and humidity, as expected in the morning versus afternoon, had a differential effect on thermoregulation and endurance performance. Eight male distance runners each participated in two heat pattern tests consisting of two hours treadmill running at 70%-maximum oxygen consumption. The mean heat load for each test was identical (22.2 degrees C wet bulb temperature) but either dry bulb temperature increased (24 to 27.5 degrees C) or decreased (27.5 to 24 degrees C) over the course of the two hour heat stress test. Whole body sweat rate was 10.7% higher (p<0.05) and there was greater plasma volume loss (2.7 versus 1.6%, p<0.05) in the cooling versus warming pattern test. Mean skin and body temperature changed in a significantly different (p<0.05) manner between the two patterns and closely followed ambient dry bulb temperature change. The thermoregulatory variables of heart rate and rectal temperature were not affected and performance did not differ between pattern tests. Ratings of perceived exertion (RPE) and oxygen consumption were also not significantly different between cooling and warming test. In summary, although some minor differences were noted, thermal homeostasis was maintained equally well during either warming or cooling for wet bulb temperatures between 24 and 27 degrees C. The mean heat load is therefore more important than changing patterns of temperature and humidity in determining an individual's physiological response to exercise in a warm environment.